Possibilities of implementing the resolution no 92/57 ES of the council of the EU ministries in Germany/Die Umsetzung der Richtlinien 92/57/ewg des EU-ministerrates in Deutschland - Seeling, Reinhard (Journal of Civil Engineering and Management, 2001)
Until now, in Germany, a construction company was in full responsibility for the fulfilment of a contract including the works performed on the contract terms. Today a person who awards a contractis is also responsible for the works performed on the contract terms. The performance of works in accordance with new terms requires additional experts who work for certain remuneration and to certain extent become the coordinators of construction. The new procedure pursues four purposes: decrease in the number of accidents, the preparation of safety of works, the integration of aspects of a contract into planning and announcing of these aspects before awarding a contract to an executor, and the engagement of the owner of construction in the procedure of settling the problems of work safety. In the course of creation this new system, the following works must be carried out: the elaborated analysis of an available situation and the settlement of a number of theoretical and practical problems. The research performed has shown that the major reasons of accidents in the course of construction comprise falling down from a big height and other events of falling down. They make up almost 40 per cent of all accidents. Over one third of these accidents occur because of the mistakes made at the stage of construction planning. Due to a new attitude to the safety of works the functions of the owner of construction are extended, the plan ensuring the safety of works and health made by a coordinator becomes necessary, mutual cooperation between the owner of construction and a coordinator as well as the qualification of the coordinator become very important. Therefore the functions of a coordinator and decisions that are to be made at the stages of planning, organizing and performing the works must be clearly outlined. To ensure the effective work of a coordinator his remuneration must be correctly calculated in accordance with the EU directives. To ensure the feasibility of this system the responsibility of all its participants must be outlined as well.Vokietijos ministrų tarybos 92/57 ES nutarimo įgyvendinimo galimybėsSantrauka. Vokietijoje visa atsakomybė už kontrakto vykdymą taip pat ir uz darbų rangą tekdavo statybos įmonei. Šiandien šia atsakomybe turi pasidalyti ir užsakovas. Tam reikia papildomų ekspertų, kurie, dirbdami už tam tikrą honorarą, tampa savotiškais statybos koordinatoriais. Nauja tvarka siekiama keturių tikslų: nelaimingų atsitikimų skaičiaus sumažinimo, darbų saugos pagerinimo, rangos aspektų integravimo į planavimą ir paskelbimo prieš pateikiant kontraktą, taip pat įtraukti statybos savininką sprendžiant darbų saugos klausimus. Kuriant šią. naują sistemą reikia atlikti išsamią esamos būklės analizę bei išspręsti nemaža teorinių ir praktinių klausimių. Tyrimai parodė, kad pagrindinė nelaimingų atsitikimų statyboje priezastis – kritimas iš didelio aukščio bei kiti kritimai. Jie sudaro beveik 40% visų nelaimingų atsitikimų. Daugiau kaip trečdalis jų atsiranda dėl klaidų statybos planavimo stadijoje. Pasikeitus požiūriui į darbų saugą išsiplečia statybos savininko funkeijos, atsiranda su juo derinamas statybos koordinatoriaus sudarytas darbų saugos ir sveikatos užtikrinimo planas, svarbi tampa statybos savininko ir koordinatoriaus tarpusavio sąveika, apskritai, paties koordinatoriaus kvalifikacija. Todėl turi būti aiškiai apibrėžtos koordinatoriaus funkcijos ir sprendimų klausimai statybos planavimo, organizavimo ir vykdymo stadijose. Siekiant efektyvaus koordinatoriaus darbo turi būti vadovaujamasi ES direktyvomis, apskaičiuojant jo honorarus. Tam, kad visa ši sistema funkcionuotų, turi būti apibrėžta visų jos dalyvių atsakomybė.Article in German.First Published Online: 30 Jul 2012